EXPERIMENTAL STUDY OF PORTABLE STOVE PERFORMANCE USE SOLAR ENERGY - Adryansyah, Rizky Sultan; Afisna, Lathifa Putri; Adimas, Fransiskus (Institut Teknologi Dirgantara Adisutjipto, 2022)
Alternative energy has begun to develop over time, such as thermal stoves that use solar energy as a heat source for cooking. The solar cooker must be of high quality, affordable, user friendly, lightweight and, stackable. A thermal solar cooker can cook a meal because the plates are heated by the sun's energy. Sunlight enters the pan or thermal solar panel and reflected toward the can or heated object. Then, Sunlight turns into heat energy.Thermal stove performance analysis was carried out starting from 09:00 WIB to 16:00 WIB. The most efficient time to use a thermal stove is 13:00 WIB, it is recorded that 350 ml of water from a temperature of 27℃ reaches a temperature of 83℃ with a heating duration of 55 minutes. One of the conclusion of this study is the time of heating influenced by weather temperature. Last, to shorten the time, then we must use the shape of sun catcher like a parabola.